2003
DOI: 10.1046/j.1365-2516.9.s1.17.x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus perspectives on prophylactic therapy for haemophilia: summary statement

Abstract: Summary. Participants in an international conference on prophylactic therapy for severe haemophilia developed a consensus summary of the findings and conclusions of the conference. In the consensus, participants agreed upon revised definitions for primary and secondary prophylaxis and also made recommendations concerning the need for an international system of pharmacovigilance. Considerations on starting prophylaxis, monitoring outcomes, and individualizing treatment regimens were discussed. Several research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
196
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(204 citation statements)
references
References 0 publications
4
196
0
4
Order By: Relevance
“…Although there are several prophylactic schemes a consensus meeting of experts held in London in 2002, helped to define ''primary prophylaxis'' as a long-term continuous treatment (intent of treating 52 weeks/year up to adulthood receiving treatment at a minimum of 46 weeks/year), started before the age of 2 years and prior to any clinically evident joint bleeding or before the onset of joint damage irrespective of age (defined as having had no more than one joint bleed) [17]. This prophylactic replacement of clotting factor has been recommended as the gold standard of care by the WFH and the World Health Organization (WHO).…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are several prophylactic schemes a consensus meeting of experts held in London in 2002, helped to define ''primary prophylaxis'' as a long-term continuous treatment (intent of treating 52 weeks/year up to adulthood receiving treatment at a minimum of 46 weeks/year), started before the age of 2 years and prior to any clinically evident joint bleeding or before the onset of joint damage irrespective of age (defined as having had no more than one joint bleed) [17]. This prophylactic replacement of clotting factor has been recommended as the gold standard of care by the WFH and the World Health Organization (WHO).…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
“…According to the literature, besides the benefit of haemophilic arthropathy prevention from prophylaxis, a marked reduction of intracranial haemorrhages, lower muscular-skeletal pain, lower rates of inpatient admissions and average of stay, improved school and work attendance and improved academic achievement have been reported [17,23]. A starting age of treatment between 1 and 2 years of age could be associated with no risk at all of developing haemarthrosis under sustained treatment [17], a Dutch cohort study that evaluated the optimal age to start prophylaxis demonstrated that an early start resulted in complete prevention of joint damage for 70 % of boys compared with 31 % for boys who started prophylaxis after three or more bleeds.…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a strong case for early prophylactic replacement of clotting factors, in the most severely affected, has been made. 17 Even small increases in clotting factor concentrations lead to a profound amelioration in the bleeding tendency. However, repeated clotting factor injections into young infants is often only possible with central venous access which carries its own hazards.…”
Section: Prevention Is Better Than Curementioning
confidence: 99%